2022
DOI: 10.26442/00403660.2022.02.201394
|View full text |Cite
|
Sign up to set email alerts
|

Visceral sensitivity in diagnostics and treatment of severe irritated bowel syndrome

Abstract: Background. Irritable bowel syndrome (IBS) is a biopsychosocial model based on the malfunction of "brain-intestinal linking". Aim. To improve diagnostics of the severe IBS accompanied with somatoform disorders by using balloon dilatation test (BDT) and optimize the therapy by using antidepressants from the serotonin and noradrenaline reuptake inhibitor type. Materials and methods. 61 patients with severe IBS and diarrhea were examined, among them 29 female with a median age of 31 years old (24; 36)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Venlafaxine, dosed for depression at 75–225 mg, acts primarily as an SSRI at lower doses, but higher doses (>225 mg) are needed to achieve NA inhibition and be effective as a pain treatment ( 22 ). Duloxetine has a strong and similar affinity for the 5-HT transporter and NA, acting as a true SNRI even at lower doses; in a comparative study, duloxetine activity was evaluated in patients with IBS-D, and the results showed a clinical remission of pain and diarrhea, as well as an increase in the threshold of visceral sensitivity, using the balloon dilation test ( 7 , 22 ). Milnacipran is more potent in inhibiting the reuptake of NA compared with its ability to inhibit the reuptake of 5-HT.…”
Section: Action Of Central Neuromodulators Determined By Class Of Agentmentioning
confidence: 99%
See 3 more Smart Citations
“…Venlafaxine, dosed for depression at 75–225 mg, acts primarily as an SSRI at lower doses, but higher doses (>225 mg) are needed to achieve NA inhibition and be effective as a pain treatment ( 22 ). Duloxetine has a strong and similar affinity for the 5-HT transporter and NA, acting as a true SNRI even at lower doses; in a comparative study, duloxetine activity was evaluated in patients with IBS-D, and the results showed a clinical remission of pain and diarrhea, as well as an increase in the threshold of visceral sensitivity, using the balloon dilation test ( 7 , 22 ). Milnacipran is more potent in inhibiting the reuptake of NA compared with its ability to inhibit the reuptake of 5-HT.…”
Section: Action Of Central Neuromodulators Determined By Class Of Agentmentioning
confidence: 99%
“…Alternatively, a secondary amine having less anticholinergic effect or duloxetine may be prescribed ( 6 , 22 ). In a randomized study conducted with 61 patients with IBS-D, SNRI-duloxetine therapy showed a significant clinical remission of pain and diarrhea ( 7 ). In patients with diarrhea where the anxiety component is predominant over pain, paroxetine could be chosen since it has greater anticholinergic effects than the other SSRIs ( 6 , 22 , 51 ).…”
Section: Targets For Treatment Based On Symptomsmentioning
confidence: 99%
See 2 more Smart Citations